THE CONTRIBUTION OF PESANTREN’S MEANING SYMBOLS AND THEIR EFFECTS ON TRANSLATION OF ARABIC TEXT - Ammar, Adzfar; Munip, Abdul; Musthofa, Tulus; B. Sapar, Ahmad Arifin; Setiyawan, Agung (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2022)
This article aims to explain the contribution of the gandul pesantren’s meaning symbols and reveal the problems in translating Arabic sentences. The method of data collection is done through observation and documentation from several sources related to the meaning of the Islamic boarding school and translation with the main data source in the form of a book entitled